2017
DOI: 10.1289/ehp1539
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Single and Combined Phthalate Metabolite Effects on Human Chorionic Gonadotropin Expression in Placental Cells

Abstract: Background:Observational studies have reported associations between maternal phthalate levels and adverse outcomes at birth and in the health of the child. Effects on placental function have been suggested as a biologic basis for these findings.Objective:We evaluated the effects of phthalates on placental function in vitro by measuring relevant candidate genes and proteins.Materials and Methods:Human trophoblast progenitor cells were isolated at 7–14 wk of pregnancy (two female and three male concepti), and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 70 publications
2
16
0
1
Order By: Relevance
“…To our knowledge, we are the first to report an impact of environmentally relevant concentrations of MEHP on human ST formation, which is essential for a fully functional placenta (Mayhew 2014). However, it is necessary to remember that organs are exposed to several phthalates that can accumulate and have additive or opposite effects, as recently described by Adibi et al. 2017b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, we are the first to report an impact of environmentally relevant concentrations of MEHP on human ST formation, which is essential for a fully functional placenta (Mayhew 2014). However, it is necessary to remember that organs are exposed to several phthalates that can accumulate and have additive or opposite effects, as recently described by Adibi et al. 2017b.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, a relatively high dose of MEHP was used (100μM and 50μM, respectively). A more recent study performed on primary VCTs showed that after 40 h of treatment with 0.7μM MEHP, hCG secretion decreased significantly in a sex-independent manner (Adibi et al. 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal exposure in rats to a mixture of environmental chemicals, including phthalates, resulted in irregular estrous cycles, reduced ovary weights, and reduced follicle numbers (Johansson et al, 2016). Human placental trophoblast progenitor cells cultured with 4 phthalate metabolites exhibited altered PPARc expression and human chorionic gonatropin levels (Adibi et al, 2017). Previously, we have cultured mouse adult antral follicles with a mixture of 6 phthalates and found alterations in gene expression as well as decreased hormone levels and increased oocyte fragmentation (Zhou and Flaws, 2016).…”
mentioning
confidence: 99%
“…PBDEs are negatively associated with total T3 and T4 in cord serum and with altered birth outcomes, including lower IQ [ 123 125 ]. Furthermore, endocrine disruptors in plastics and personal care items, including phthalates and bisphenol A, have been shown to affect TH regulation including impairment of iodine uptake and inhibition of TH homeostasis [ 126 ] and phthalates have been found to be associated with hCG, glucose intolerance, and GDM [ 127 129 ].…”
Section: Discussionmentioning
confidence: 99%